Daya Serap Pelaksanaan Mata Kuliah Kependidikan DiTengah Pandemi Covid-19 - Kholisho, Yosi Nur; Marfuatun, Marfuatun (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
Covid-19is a new virus that attacks the whole world. The virus has paralyzed all areas of life. Based on the circular of the Minister of education and culture of the Republic of Indonesia Number 2 and 3 of 2020, the learning is done online at home. Good student absorption can improve student learning outcomes. The purpose of this study is to look for points of concern about students' absorption of educational lectures using online methods viewed from internal and external factors. This research uses a descriptive method. The sample used was 67 respondents. Our findings showÂ theÂ students who have been ill while attending lectures is less interested in educational subjects being an internal factor that can affect student absorption, but strong student confidence in passing courses makes this factor not inhibiting factor students, while external factors are factors that affect the absorption of students taking educational courses with the online method in the middle of the covid-19 pandemic. Disruptions of the family economy caused by parents who cannot work in the middle of a pandemic are the main things that affect the lecture process. Parental support is less than optimal, as well as the location of the house that makes the signal often lost and entered.